Biochemical and molecular targets of dysfunction on fatty acid transport and mitochondrial oxidation induced by steatogenic drugs - Aires, Cátia Cordeiro Pinto, 1979- (2010)
Tese de doutoramento, Farmácia (Bioquímica), Universidade de Lisboa, Faculdade de Farmácia, 2010